When the going gets tough, the tough gets going: COVID 19 and ASEAN’S Effort / Suseela Devi Chandran, Farhatul Mustamirrah Mahamad Aziz and Azman Ayob - Chandran, Suseela Devi; Mahamad Aziz, Farhatul Mustamirrah; Ayob, Azman (2021)
There is one phrase that nearly every leader and foreign minister of ASEAN (Association of Southeast Asian Nations) has used to describe the management of the region's security issues: the ‘ASEAN Way’. At the meetings of ASEAN, when a question was posed to the ASEAN foreign ministers, for instance, how ASEAN intended to deal with the political turmoil and the military coup d’état in Myanmar now - the answer was: “We deal with all our members the ASEAN Way. It will be no different with Myanmar”. The ASEAN Way theme has been echoed among ASEAN leaders for the past few decades. The states in the Southeast Asia region perceive there are unique or “different predominant strategic preferences” for managing security. However, despite such conclusions, some commentators argue otherwise. According to these analysts, the notion of the ASEAN Way was simply exaggerated and fallacious. These analysts argue that one of the most critical foundations that underpin ASEAN’s credibility as a regional organisation is its capacity to play a central role in addressing regional affairs and in shaping the regional order. According to these skeptics, ASEAN continues to pay lip service to its myriad principles, norms, and aspirations, especially about issues like pandemic Covid 19. So, to what extent ASEAN as a regional organisation has stood to the common English proverb that says, “When the going gets tough, the tough get going”. From the still raging COVID-19 pandemic to the current scramble for the virus vaccines, from the ongoing tensions in the South China Sea to the February 2021 military coup in Myanmar one shock after another has hit the region. How resilient is ASEAN as a regional institution to deal with such issues? The objective of this paper is to analyse how ASEAN as a regional organization has addressed the Covid19 pandemic individually and collectively. The paper first, explores the nature of the ASEAN Way, and second, apply the conceptual discussion to the case of the Covid-19 pandemic to show the efforts made by ASEAN